Consistency Analysis of Rendement and Quality of CPO (Crude Palm Oil) Palm Oil Processing at PT. Agricinal North Bengkulu - Johannes Agung Sitorus; Andwini Prasetya Prasetya; Hesti Nur'aini; Diah Azhari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
The yield and quality of CPO is influenced by the condition of unripe and overripe FFB (fresh fruit bunches), which can cause an increase in ALB, water content and dirt content. The quality of CPO is also influenced by FFB from the community. Analysis of the consistency of the yield and quality of CPO was carried out due to the age of the plants that were too old and the performance of the factory machines decreased due to the age of the machines. Analysis of yield consistency and quality was carried out using statistical quality control methods, namely quality control using a statistical approach using control charts and causal diagrams. This study uses secondary data on the yield and quality of CPO for the past year (July 2021-June 2022). The research results show, there are data that are outside the upper control limit, yield in July 2021, free fatty acid content in May 2022 and dirt content in October 2021. While the water content is statistically controlled (in statistical control). The yield and quality of ALB are influenced by type of raw material, production capacity and oil losses. Moisture content and dirt content are affected by treatment of production process and machine conditions.